2015
DOI: 10.1590/1516-635x1703333-340
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Growth and Mineralization of the Femur, Tibia, and Metatarsus of Broiler Chicks

Abstract: This study aimed at comparing the growth and mineralization of the femur, tibia, and metatarsus of male and female broiler chicks. On the day of hatch, 100 male and 100 female Ross 308 broiler chicks were transferred stainless cages with 10 birds per cage. On d 7, 14, 21, 28, 35, and 42, five males and five females were sacrificed and their femur, tibia, and metatarsus were collected. Results showed that the tibia was the heaviest and the longest and contained the highest content of ash and calcium (Ca) among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
2
9
0
1
Order By: Relevance
“…This outcome meant that the keel bone growth in length increased from 29.9 mm at 1 day to 147.5 mm at 35 days of age, but the third toe growth in length increased from 24.2 mm at 1 day to 62.6 mm at 35 days of age. Several studies have evaluated longitudinal bone growth in broiler chickens (Applegate and Lilburn, 2002;Biesiada-Drzaga et al, 2012;Shim et al, 2012;Han et al, 2015;Mabelebele et al, 2017). The results of previous studies were similar to the obtained results in the current study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This outcome meant that the keel bone growth in length increased from 29.9 mm at 1 day to 147.5 mm at 35 days of age, but the third toe growth in length increased from 24.2 mm at 1 day to 62.6 mm at 35 days of age. Several studies have evaluated longitudinal bone growth in broiler chickens (Applegate and Lilburn, 2002;Biesiada-Drzaga et al, 2012;Shim et al, 2012;Han et al, 2015;Mabelebele et al, 2017). The results of previous studies were similar to the obtained results in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The results of previous studies were similar to the obtained results in the current study. That is, the absolute bone growth in length in the broiler chickens was positively increased with age (Biesiada-Drzaga et al, 2012;Han et al, 2015) or with body weight (Applegate and Lilburn, 2002;Paxton et al, 2014;Mabelebele et al, 2017). The present study also indicated that the rate of longitudinal bone growth differed depending on the studied bones.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Shim et al (2012) stated that bone of fast-growing broiler at 6 weeks age is longer, wider, heavier, stronger, compact and high calcium concentrated compared with slow-growing broiler with the same age. Han et al (2015) stated that tibia is the longest and heaviest part compared with femur as the longest diameter bone. Mortality rate and performance of broiler-type chicken are affected by bone structure.…”
Section: Resultsmentioning
confidence: 99%
“…Frangos de corte de crescimento rápido são caracterizados por maior ganho de peso corporal, o que resulta em problemas no esqueleto (principalmente ossos do fêmur e da tíbia) que desempenham um papel importante como estrutura de suporte para seu peso corporal, tais problemas ósseos podem reduzir o desempenho do crescimento dos frangos de corte e aumentando a mortalidade (HAN et al, 2015).…”
Section: Introductionunclassified